(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Every student studying at a higher educational institution should be able to freely express their opinion in public. If this is not normal, that is, a student cannot speak at seminars, defense of scientific papers, and even at spiritual and educational events, then it indicates a speech deficit. Existing practical experience of teachers of pedagogical disciplines, as well as individual training in the didactics of higher education institutions theoretical provisions on the methodology of teaching pedagogy, principles, rules, and recommendations have been systematized.